PENGGUNAAN MEDIA SOSIAL DALAM PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMA NEGERI 9 MALANG DI MASA PANDEMI COVID-19 - Ilmiyatin Nafi’ah; Mohammad Hanief; Eko Setiawan (VICRATINA, 2021)
The use of social media as a tool for distance learning is a new thing for teachers and students at SMA Negeri 9 Malang since the COVID-19 pandemic. The focus of this study discusses the use of social media, learning motivation, and the factors supporting and inhibiting the use of social media in the learning process of Islamic religious education. To achieve this goal, the researcher used a qualitative approach using a case study type of research. The application of this research includes the application used, and increasing learning motivation. The supporting factors for this research are adequate infrastructure. The inhibiting factor for this research was not being able to meet face-to-face with students directly because of the covid-19 pandemic, so it was done by video calling.